The New Regulation D: Deregulation, Federalism and the Dynamics of Regulatory Reform - Mark A. Sargent (Washington University Law Quarterly, 1990)
Over the course of 1987-1989 the Securities and Exchange Commission (SEC) created a new Regulation D. While the basic structure of this important set of exemptions from securities registration under the Securities Act of 1933 (the 1933 Act) remains essentially unchanged, the combined force of numerous revisions of existing rules and the introduction of the novel "substantial compliance" concept has shaped a distinctly different legal environment for exempt transactions. We now need a guide to that unsettled environment, one that explains the points of departure, the changes of direction and the still uncharted territory. This Article will try to provide such a guide. Part II creates a basis for further analysis by briefly describing Regulation D as it stood prior to the 1987-1989 revisions. This description of the setting for change will provide a working vocabulary of the exemptive concepts used under the Regulation. Part III examines the background to change by tracing the evolution of Regulation D and showing how conflicting attitudes about the need for reform and the appropriate mechanisms of reform shaped the revision process. In particular, Part III argues that the central dynamic shaping the new Regulation D was a dialectical conflict between the securities bar and the state securities administrators, with the SEC playing a crucial mediating and synthesizing function. This argument will show the pervasive impact of questions of federalism on regulatory policy toward exempt transactions. Part IV explains the basic principles applied in revising the rules and identifies new interpretive problems. Part V contends that both the recent revisions and the basic structure of Regulation D make sense as positive attempts to balance the costs and benefits of securities regulation and to achieve a rational allocation of regulatory responsibilities between the states and the SEC. This Article concludes in Part VI by identifying the unfinished agenda and recommending solutions to those problems left unresolved by the 1987-1989 revisions to Regulation D.
Keywords: Securities